Diet quality, nutritional status, and psychological symptoms in Argentine adolescents: A comparative study of urban and rural settings - Noelia Natalia Fernández; Silvia Estela López; Ana Betina Lacunza (Nutrition and Health, 2026)
Background Adolescent overweight and obesity are critical public health challenges linked to psychological distress, yet their interplay remains understudied in Global South contexts. Aim To assess the relationship between diet quality, nutritional status, and psychological symptoms among adolescents in urban and rural areas of Tucumán, Argentina. Methods A cross-sectional study was conducted with 535 adolescents (12–19 years). Assessments included body mass index, waist circumference, the Índice de Calidad de la Alimentación y Protección en Adolescentes (ICAPA), and the adolescent personality assessment inventory. Summary Overweight/obesity prevalence was 42.4%, being higher in males and rural settings; 32% exhibited cardiometabolic risk. Most participants (59.3%) had an unhealthy diet. Males scored significantly higher in somatic complaints, anxiety, depression, and aggression ( p < 0.05). Urban adolescents showed higher mania and dominance, while rural counterparts reported higher suicidal ideation and substance problems ( p < 0.05). Notably, normal-weight adolescents exhibited higher antisocial traits than those with excess weight ( p < 0.05). Correlation analyses revealed significant negative associations between diet quality and depression, antisocial traits, aggression, and suicidal ideation. Specifically, diet quality was negatively correlated with suicidal ideation in the clinical group, and with somatic complaints and aggression in the control group ( p < 0.05). The coexistence of poor diet, excess weight, and psychological symptoms underscores the need for integrated, school-based interventions tailored to specific socio-geographic environments and nutritional statuses.